Forms of Verbal and Non-Verbal Communication in Toxic Relationships in Teenage Dating Relationships (Literasi Nusantara, 2025)
This study examines verbal and non-verbal communication patterns in toxic adolescent romantic relationships, identifying the factors that compel teenagers to remain in such dynamics and assessing the resulting emotional and social impacts. Employing a qualitative phenomenological approach, the researchers conducted in-depth interviews, non-participant observations, and documentation with eight informants (aged 18–23) in East Java who have experienced toxic dating environments. The findings categorize toxic communication into two spheres  Characterized by manipulation, blaming, demeaning language, and implicit threats. Non-Verbal: Marked by high-pitched intonation, aggressive expressions, "silent treatment," and restricted social interactions. Despite these harms, participants often remained in these relationships due to emotional dependency, fear of abandonment, and the dangerous normalization of toxic behavior, misinterpreting control as a form of affection. Toxic communication patterns profoundly damage adolescent well-being, leading to diminished self-esteem, heightened anxiety, and social withdrawal. The study highlights that interpersonal communication is the primary vehicle through which toxic dynamics are both constructed and sustained, emphasizing the need for healthier relationship literacy among youth.